Metabolic syndrome and risk factors for non-alcoholic fatty liver disease - Souza,Mônica Rodrigues de Araújo (2012)
CONTEXT: Non-alcoholic fatty liver disease (NAFLD), hepatic manifestation of metabolic syndrome, has been considered the most common liver disease nowadays, which is also the most frequent cause of elevated transaminases and cryptogenic cirrhosis. The greatest input of fatty acids into the liver and consequent increased beta-oxidation contribute to the formation of free radicals, release of inflammatory cytokines and varying degrees of hepatocytic aggression, whose histological expression may vary from steatosis (HS) to non-alcoholic steatohepatitis (NASH). The differentiation of these forms is required by the potential risk of progression to cirrhosis and development of hepatocellular carcinoma. OBJECTIVE: To review the literature about the major risk factors for NAFLD in the context of metabolic syndrome, focusing on underlying mechanisms and prevention. METHOD: PubMed, MEDLINE and SciELO data basis analysis was performed to identify studies describing the link between risk factors for metabolic syndrome and NAFLD. A combination of descriptors was used, non-alcoholic fatty liver disease, non-alcoholic steatohepatitis, metabolic syndrome and risk factors. At the end, 96 clinical and experimental studies, cohorts, meta-analysis and systematic reviews of great impact and scientific relevance to the topic, were selected. RESULTS: The final analysis of all these data, pointed out the central obesity, type 2 diabetes, dyslipidemia and hypertension as the best risk factors related to NAFLD. However, other factors were highlighted, such as gender differences, ethnicity, genetic factors and the role of innate immunity system. How these additional factors may be involved in the installation, progression and disease prognosis is discussed. CONCLUSION: Risk factors for NAFLD in the context of metabolic syndrome expands the prospects to 1) recognize patients with metabolic syndrome at high risk for NAFLD, 2) elucidate pathways common to other co-morbidities, 3) determine risk factors associated with a worse prognosis, 4) develop therapeutic strategies with goal of reducing risk factors, 5) apply acquired knowledge in public health policies focusing on preventive strategies.